The harder we fall : the We Company's 2019 IPO fiasco - Markovich, Sarit; Meagher, Evan (London : Kellogg School of Management, 2021)
The case describes WeWork's by-now-infamous fall from grace, during the turbulent autumn of 2019. Governance, financial strategy, and ethics are all prominent themes. WeWork had been a dominant player in the coworking office space market and had tried to create an ecosystem that allowed tenants of its office space to collaborate easily with one another, as well as one that offered third-party services. The case allows instructors to discuss commercialization strategies, boundaries of the firm, and issues related to investors in private versus public markets.
Orginally Published InMarkovich, S., & Meagher, E. (2021). The Harder We Fall:The We Company's 2019 IPO Fiasco. 5-120-001. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; WeWork (Firm) -- Case studies; Investments -- Case studies